2003
DOI: 10.1103/physreve.67.056218
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for directed percolation universality at the onset of spatiotemporal intermittency in coupled circle maps

Abstract: We consider a lattice of coupled circle maps, a popular model for the study of mode-locked phenomena. We find that the onset of spatiotemporal intermittency (STI) in this system is analogous to directed percolation (DP), with the transition being to a unique absorbing state for low nonlinearities, and to weakly chaotic absorbing states for high nonlinearities. We find that the complete set of static exponents and spreading exponents at all critical points match those of DP very convincingly. Further, hyperscal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…It has been shown convincingly that STI with synchronized laminar state interspersed with turbulent bursts (seen at points marked with ✸ in Figure 1) belongs to the DP universality class [17,18]. The infective dynamics of the turbulent bursts wherein the turbulent site either infects the adjacent laminar sites, or dies down to the laminar state, is similar to the behaviour seen in directed percolation [22].…”
Section: A Sti Of the Dp Typementioning
confidence: 55%
See 3 more Smart Citations
“…It has been shown convincingly that STI with synchronized laminar state interspersed with turbulent bursts (seen at points marked with ✸ in Figure 1) belongs to the DP universality class [17,18]. The infective dynamics of the turbulent bursts wherein the turbulent site either infects the adjacent laminar sites, or dies down to the laminar state, is similar to the behaviour seen in directed percolation [22].…”
Section: A Sti Of the Dp Typementioning
confidence: 55%
“…Earlier studies of the diffusively coupled sine circle map lattice showed regimes of STI which were completely free of solitons [17,18]. Two types of STI were seen along the bifurcation boundaries of the bifurcation from the synchronized solution.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Coupled map systems show many of the varied phenomena observed in the case of continuous extended systems, but are far more numerically and analytically tractable. Coupled map systems have been seen to show synchronised solutions, spatiotemporal intermittency, spatiotemporal chaos [13,14]. However, to the best of our knowledge, chimera states have not been reported earlier in coupled map lattice systems.…”
Section: Introductionmentioning
confidence: 75%